THE RELATIONSHIP BETWEEN AUDIT PROCEDURES, AUDITORS’ EXPERIENCE AND AUDITORS’ RESPONSIBILITY FOR FRAUD DETECTION - Naufal Hazim Widodo; Anis Chariri (Diponegoro Journal of Accounting, 2021)
This study investigates the relationship between audit procedures, auditors’ experience, and auditors’ responsibility for fraud detection. Auditors’ responsibility for fraud detection act as the dependent variable, whereas the independent variables, are audit procedures and auditors’ experience. The control variables of the study are gender and position. Empirical test results are obtained from auditors as respondents working at fourteen public accounting firms in Indonesia. The findings show that the audit procedures and auditors’ experience positively influence the auditors’ responsibility for fraud detection. This study contributes to auditing and accounting literature, precisely the fraud detection method, which is used to increase the awareness of fraud risk